English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-26 15:44:45 · 2 answers · asked by Olivia 4 in Science & Mathematics Mathematics

2 answers

Let u=6/x. Then du = -6/x^2, and you have

integral of -e^u du = -e^u + C = -e^(6/x) + C

2006-10-26 15:47:38 · answer #1 · answered by James L 5 · 1 0

ewwwwww.....geez i forgot how to do that and i did that stuff last year x_x sorry

2006-10-26 22:47:59 · answer #2 · answered by ssj4gokugirl 2 · 0 0

fedest.com, questions and answers